Kajian Pertunjukan Musik â€œThungkaâ€ dalam Tinjauan Etnomusikologi - Hafi Hilmiah Almanda; Setya Yuwana; Setyo Yanuartuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the study was to find an ethnomusicological study and to find out everything contained in the Thungka musical instrument, whether it was in the form of functional, musical, instrumental and socio-cultural aspects. The research method is a qualitative descriptive method with an ethnomusicological approach. Sources of data used in this study were video recordings of the performance of the traditional performing arts of Thungka music by the people of Bawean Gresik, as well as interviews, documentation, and literature studies. The results showed that basically Thungka had a function as a rice pounder in the annual harvest season, but now it has become a medium for traditional art performances, weddings, to welcoming tourist guests to Bawean. Thungka traditional music describes the socio-cultural life of the Bawean people, especially the gratitude of the farmers and in the lyrics also tells the feeling of waiting and longing. The conclusion of this research is that the dynamics used when playing Thungka traditional musical instruments are forte and fortisisimo. Alu' and Ronjengan from traditional musical instruments Thungka made of teak. The way of making it using original human power by using chisels and crab bolsters in the way of making musical instruments. Keywords: Bawean, Ethnomusicology, Thungka Music